Pertanggungjawaban Hukum Notaris atas Pembuatan Akta di Luar Wilayah Jabatan dalam Perspektif Kepastian Hukum - Indah Ayu Silvyana; Umar Hasan; Meri Yarni (LPPM Institut Pendidikan Nusantara Global, 2026)
The territorial authority of notaries in Indonesia is regulated in Law No. 30 of 2004 concerning Notary Positions, as amended by Law No. 2 of 2014. This territorial limitation aims to ensure that the deeds made by notaries have valid evidentiary power and do not exceed the granted authority. However, the practice of making deeds outside the territorial jurisdiction still occurs, leading to legal issues regarding the validity and legal certainty of such deeds. This study aims to analyze the legal responsibility of notaries who create deeds outside their territorial jurisdiction and the implications that arise from such actions. The research employs a normative legal method with statutory and conceptual approaches. The findings indicate that making a deed outside the designated jurisdiction may be considered ultra vires, resulting in the deed losing its authentic nature and being inadmissible as legal evidence in court. Additionally, notaries may face civil, administrative, and professional ethical sanctions. This study emphasizes the importance of strict supervision over notarial jurisdiction to maintain the integrity of the profession and protect the legal rights of the public. In conclusion, the regulation of territorial authority for notaries must be enforced rigorously to ensure legal certainty and prevent harm to the parties involved.